KEPEMIMPINAN KRISTEN DAN NILAI-NILAI HAK ASASI MANUSIA SEBAGAI STRATEGI TEOLOGIS DALAM MENANGKAL RADIKALISME - Elisa Nimbo Sumual; Yohana Fajar Rahayu; Semuel Ruddy Angkouw (Sekolah Tinggi Teologi Arastamar Bengkulu, 2025)
Radicalism developing within religious educational institutions poses a serious threat and challenge to social life and harmony. Religious institutions, which should serve as spaces for character building and spirituality, have the potential to become fertile ground for the spread of extremist ideologies and hatred. The failure to integrate universal human values and theology that respects others is one of the main causes of the weakness of religious organisations. Moreover, the phenomenon of increasing intolerance among the younger religious generation shows a crisis in moral leadership and education based on religious teachings. This study aims to examine the strategic role of Christian leadership and human rights education as a theological approach to countering radicalism in religious educational institutions. Using a descriptive qualitative method based on literature review, it can be concluded that the role of Christian leadership theology as the foundation of anti-radicalism and human rights education from a Christian theological perspective are interdependent elements that must be integrated, encompassing both Christian leadership and human rights education. This serves as a preventive theological strategy, thereby presenting both the value of implementation and the challenges of theological strategy within religious educational institutions.